1967
DOI: 10.1080/09553006714551341
|View full text |Cite
|
Sign up to set email alerts
|

Protection against X-irradiation by Sulphydryl Compounds

Abstract: The radioprotective effect of eight thiol compounds with pK-values of their thiol groups varying from 8'5-10'8 was tested on isolated cells in vitro. The influence of variations in pH of the incubation medium between 6-3 and 83 was investigated. The ability of the cells to form colonies was used as the criterion for survival.By comparing the protection affected by different concentrations of the various compounds it was found that a good correlation existed between the degree of radio-protection and the thiola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1969
1969
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Unless these analogs are taken into the cell by some stereoselective process these data argue against the proposal that the degree of radioprotection is only dependent upon the intracellular thiolate ion concentration. 52 The greater activity of trans-2, -3, and -4 (5 mM concentration) over MEA (1) might be due to increased thiolate ion concentration owing to increased absorption of the more lipophilic cyclobutanes. However, trans-2 and -4 have significantly different radioprotective activities (Table III) but similar pKa's and predicted lipid solubilities.…”
Section: Discussionmentioning
confidence: 99%
“…Unless these analogs are taken into the cell by some stereoselective process these data argue against the proposal that the degree of radioprotection is only dependent upon the intracellular thiolate ion concentration. 52 The greater activity of trans-2, -3, and -4 (5 mM concentration) over MEA (1) might be due to increased thiolate ion concentration owing to increased absorption of the more lipophilic cyclobutanes. However, trans-2 and -4 have significantly different radioprotective activities (Table III) but similar pKa's and predicted lipid solubilities.…”
Section: Discussionmentioning
confidence: 99%
“…O H radicals and oxygen (as 0-,) this may be one of the important properties which determines whether or not a compound is radio-protective. In this connection it is interesting to note that Vos et al (5) found that penicillamine protected cells almost as well as cysteine under anoxic conditions (i.e. in the absence of 0-,).…”
Section: Discussionmentioning
confidence: 99%
“…Reactions [l] and [2] seem to occur with both cystine and penicillamine disulfide although reaction [XI may be more important than [ I ] in the case of penicillamine disulfide. Reactions [3], [4], and [5] probably occur with both CySOH and PenSOH and reaction [5] could be one of the reactions leading to the symmetrical disulfides. Reaction [6] is more specific as it does not occur with PenSOH.…”
Section: Discussionmentioning
confidence: 99%
“…Takagy et al (1974), in experiments conducted on Hela cells observed that the genotoxicity of MEA at low concentrations developed gradually over time during which hydrogen peroxide was generated in the medium, with the addition of catalase and peroxidase inhibiting this "paradoxical" effect. Vergroesen et al (1967), demonstrated that thiols with a pK value of less than 10 were toxic at concentrations of 0.1 and 2.0 mM, with the addition of another thiol at high concentrations, the lowering of the pH or the presence of KCN (which has no radioprotective power and has no effect on the radioprotective action of SH compounds), eliminating the toxicity. Whereas the addition of Na 2 S 2 O 3 (which does not penetrate the cell) to the system does not change the toxic condition, a fact probably indicating that this toxicity may be due to a process occurring at the intracellular level, possibly of an oxidative nature.…”
Section: Discussionmentioning
confidence: 99%
“…MEA can protect mammalian cells from radiologic phenomena such as cell death (Barendsen, 1964;Eker and Pihl, 1964;Vergroesen et al, 1967;Sinclair, 1967;1968;Vos, 1969), mitotic delay (Firket and Mathieu, 1966), chromosome aberrations (Yang and Hahn, 1968;Vos and Kaalen, 1968) and depression of DNA synthesis (Honjo, 1963). Santos-Mello (1977) reported that MEA can also inhibit DNA repair (unscheduled DNA synthesis -UDS) as well as the repair of radioinduced chromosome breaks in human lymphocytes.…”
Section: Introductionmentioning
confidence: 99%